The Effect of Supplementing White Sweet Lupine Grain Meal (Lupinus albus L.) on Blood and Milk Metabolites, Milk Yield, and Quality of Dairy Cows in Ethiopia - Birhan, Malede; Mekuriaw, Yeshambel; Tassew, Asaminew; Tegegne , Firew (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Feed is the cornerstone of dairy production, serving as a crucial input for sustainable milk production. This trial aimed to investigate the effect of white sweet lupine grain meal inclusion on feed intake, blood and milk metabolites, milk yield, and quality. The experimental cows had a parity of 2±0.71 (mean ± SD), a daily milk yield of 12.72 ± 0.9, and an average body weight of 412.6 ± 21.5 kg. The varying proportions of treatment diets were: 75, 50, 25 and 0% (T1, T2, T3 and T4) treatment groups respectively. Data collected during the study were subjected to analysis of variance to determine significant differences. Cows fed diet T1 showed a better dry matter (10.39 kg/day), organic matter (7.31 kg/day), nitrogen (2.42 kg/day), and NDF intakes (3.75 kg/day) that had significant difference on (p<0.05). When lupine inclusions dropped from 75 to 50 and even to 25%, the N digestibility decreased from 76.63, 70.66, and 65.6%, respectively, and the digestibility of N in all treatment diets significantly decreased (p < 0.01). Once more, cows fed T1 diet had the highest (p<0.01) plasma glucose concentration (116.81 mg/dl) among the four experimental groups. Cows fed T2 and T4 diets showed significant variation at (p<0.05) in plasma glucose levels, with values of 108.7 and 110.16 mg/dl, respectively. Cows fed T1 had relatively lower plasma beta-Hydroxybutyric acid and non-esterified fatty acid concentrations (p<0.05) than others, with mean values of 3.23 and 1.28 mg/dl respectively. The partial inclusion of white sweet lupine grain meal up to the level of 75% is highly suggested as a better alternative feed source.